THE ANALYSIS OF DIFFERENCES IN DOCTORS PREFERENCES IN THE PRESCRIPTIONS OF ANTIHYPERTENSIVE DRUGS IN FOUR REGIONS OF THE FAR EASTERN FEDERAL DISTRICT - M. S. Soboleva; Е. E. Loskutova (Рациональная фармакотерапия в кардиологии)
Aim. To study regional features and preferences of specialists in the choice of drug therapy of arterial hypertension in four subjects of the Far Eastern Federal District.Material and methods. Statistical data, demographic indicators, state and municipal drug procurements in Chukotka Autonomous Okrug, the Sakha Republic (Yakutia), the Magadan Region, and Kamchatka Krai were analyzed. The studied period was 2012-2016. Dynamics of the use (procurements) of five main therapeutic classes of antihypertensive drugs was studied.Results. Among β-blockers the leaders were metoprolol (from 2% to 30.8%) and bisoprolol (from 2.4% to 20.3%); in group of angiotensin converting enzyme inhibitors – enalapril (from 3.6% to 27%), lisinopril (from 4.4% to 23.9%) and perindopril (from 0.9% to 7.8%); among calcium channel blockers – amlodipine (from 5.6% to 11.3%); in group of diuretics – indapamide (from 2.5% to 13%) and spironolactone (from 3% to 12.5%), and in group of angiotensin II antagonists – losartan (from 0.4% to 15.6%). Angiotensin converting enzyme inhibitors were the most used therapeutic class of antihypertensive drugs in Chukotka Autonomous Okrug, the Magadan region and Kamchatka Krai. At the same time, β-blockers accounted for more than a half of state and municipal procurements in the Sakha Republic (Yakutia).Conclusion. It is necessary to study regional aspects and approaches to therapy to assess the extent and specificity of the implementation of research results, standards and recommendations in real clinical practice.